Financial Reporting and Auditing Under Alternative Damage Apportionment Rules - Hillegeist, Stephen A. (The Accounting Review, 1999)
This article analyzes the impacts that three alternative damage apportionment rules have on an owner's financial-reporting decision, an auditor's audit-quality choice, and investors' pricing decisions within the context of a perfectly competitive securities market and owner solvency constraints. The strategic interactions between the players' strategies are analyzed within a setting where payoffs are endogenously determined and vary with the damage apportionment rule. These comparisons speak to potential changes resulting from the Private Securities Litigation Reform Act of 1995 which replaced joint-and-several liability with a proportionate liability rule. The main finding is that the audit failure rate can decrease when there is a switch from a joint-and-several to a proportional liability rule despite the fact that audit quality has also declined. This result occurs when there are strategic interactions between the owner's reporting strategy and the auditor's quality decision.